Unlocking the Mind's Language: Exploring Cognitive Linguistics and Language Processing - Shafira Azzahrah (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This paper explores the field of cognitive linguistics and its implications for language processing. The study aims to uncover the underlying mechanisms of the mind's language through a comprehensive review of existing literature. Methods: The methodology involves a qualitative analysis of key concepts and theories in cognitive linguistics, such as conceptual metaphor, image schemas, and mental spaces. Results: The results reveal that cognitive linguistics offers valuable insights into how language is processed and understood by the human mind. The findings suggest that language is not merely a system of symbols but a reflection of cognitive processes. Conclusions: In conclusion, this study highlights the importance of cognitive linguistics in unlocking the mysteries of language and cognition.